Gender, Power, and Education: A Critical Literature Review of Sociological Theories on Gender Inequality in Schools - Hikmat (Jurnal Abdimas Peradaban, 2023)
This study critically examines the intersection of gender, power, and education through a comprehensive review of sociological theories addressing gender inequality in schools. It highlights how schools often serve as sites where structural power relations reproduce existing social hierarchies, thereby reinforcing gender disparities. The literature review method was employed to synthesize theoretical perspectives and empirical findings from diverse academic sources. Key sociological frameworks, including functionalism, conflict theory, feminist theory, and intersectionality, provide a multidimensional understanding of the issue. The analysis reveals that schools not only transmit knowledge but also perpetuate social norms that privilege male authority and marginalize female voices. A critical reading of existing scholarship demonstrates both the strengths and limitations of these theories in explaining persistent inequalities. Moreover, the review identifies gaps in integrating intersectional perspectives that account for race, class, and cultural diversity within educational contexts. By foregrounding these dynamics, the study underscores the role of education as both a site of oppression and potential empowerment. The findings emphasize the need for transformative pedagogical practices and inclusive policies that challenge traditional power structures. Ultimately, this review contributes to advancing sociological debates on gender and education by mapping theoretical developments and suggesting directions for future research.